A multi-level converter with a floating bridge for open-ended winding motor drive applications - Chowdhury, Shajjad; Wheeler, Patrick; Patel, Chintanbai; Gerada, C. (Institute of Electrical and Electronics Engineers, 2016)
This paper presents a dual three phase open end winding induction motor drive. The drive consists of a three phase induction machine with open stator phase windings and dual bridge inverter supplied from a single DC voltage source. To achieve multi-level output voltage waveforms a floating capacitor bank is used for the second of the dual bridges. The capacitor voltage is regulated using redundant switching states at half of the main dc link voltage. This particular voltage ratio (2:1) is used to create a multi-level output voltage waveform with three levels. A modified modulation scheme is used to improve the waveform quality of this dual inverter. This paper also compares the losses in dual inverter system in contrast with single sided three-level NPC converter. Finally, detailed simulation and experimental results are presented for the motor drive operating as an open loop v/f controlled motor drive and as a closed loop field oriented motor controller.